Land Capability Analysis for Sustainable Land Use Planning: A Case Study of Bogor Regency, Indonesia - Auliya, Izhar; Widiatmaka; Syartinilia (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Uncontrolled land use changes can lead to mismatches with designated spatial patterns, resulting in critical land issues such as erosion and flooding. Bogor Regency has undergone rapid land use transformations, particularly in agriculture, with significant shifts occurring between 1995 and 2001. This study evaluates land capability using a matching and scoring approach to determine its suitability concerning existing spatial patterns. Key factors such as slope, erosion hazards, and soil depth were analyzed to classify land into capability categories. The findings reveal six classes of land capability, ranging from Class II to VII, with Classes IV and VI being the most dominant. Spatial analysis indicates that a large portion of Bogor Regency's land cover aligns well with its land capability. Compatibility with designated spatial patterns is predominantly conditional, suggesting that some areas may require mitigation measures or adjustments for sustainable development. The conditional suitability of land capability with spatial patterns highlights the need for careful planning interventions. Decision-makers must consider land constraints and adopt adaptive land-use policies to mitigate risks such as erosion and flooding. Integrating land capability assessments into planning frameworks can enhance sustainable land management and minimize environmental degradation.